Investigation of oxidation processes in non-stoichiometric lithium-titanium ferrites using TG analysis; Journal of Thermal Analysis and Calorimetry; Vol. 102, iss. 3 - Surzhikov A. P. Anatoly Petrovich; Frangulyan (Franguljyan) Т. S. Tamara Semenovna; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Lysenko E. N. Elena Nikolaevna (2010, 2010)
Title screen